2022
DOI: 10.3390/ph15111378
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosols of Veronica Species—Natural Source of Free Volatile Compounds with Potential Pharmacological Interest

Abstract: In this study, free volatile compounds (FVCs) were isolated from the water fractions (hydrosols) of 10 Croatian Veronica species obtained by hydrodistillation (HD) and microwave-assisted extraction (MAE). The use of different isolation techniques is important for the analysis of the influence of extraction conditions on the qualitative and quantitative composition of the isolated constituents. The composition of the hydrosols was analyzed using gas chromatography and mass spectrometry. The compounds β-ionone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 45 publications
0
16
1
Order By: Relevance
“…In that research, the composition of oil components obtained by classical (Clevenger apparatus, HD) and modern hydrodistillation (MAE) was compared, so the value of hexahydrofarnesyl acetone in the EO of V. anagalloides was 14.33% for HD and 19.12% for MAE [ 2 ]. Moreover, in Nazlić et al article [ 7 ], a much lower β -ionone relative percentage was found in this sample obtained by MAE compared to this study: only 4.22%.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…In that research, the composition of oil components obtained by classical (Clevenger apparatus, HD) and modern hydrodistillation (MAE) was compared, so the value of hexahydrofarnesyl acetone in the EO of V. anagalloides was 14.33% for HD and 19.12% for MAE [ 2 ]. Moreover, in Nazlić et al article [ 7 ], a much lower β -ionone relative percentage was found in this sample obtained by MAE compared to this study: only 4.22%.…”
Section: Discussioncontrasting
confidence: 65%
“…The FVCs of the other five Veronica species studied in this paper were compared with previously published data [ 2 , 7 , 28 ]. In the composition of the EO extract of V. anagalloides , the dominant compounds are hexahydrofarnesyl acetone (16.17%) and β -ionone (13.13%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations